2021
DOI: 10.1136/bmjopen-2020-043637
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to cervical cancer prevention in rural Cameroon: a qualitative study on healthcare providers’ perspective

Abstract: ObjectiveCervical cancer in Cameroon ranks as the second most frequent cancer among women and the leading cause of cancer-related deaths, mainly due to the lack of prevention. Our principal objective was to explore potential barriers to an human papillomavirus (HPV)-based cervical cancer screening from a healthcare provider (HCP) perspective in a low-income context. Second, we aimed to explore the acceptability of a single-visit approach using HPV self-sampling.SettingsThe study took place in the District hosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
49
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(50 citation statements)
references
References 20 publications
1
49
0
Order By: Relevance
“…Moreover, under the private initiative of civil society organizations (CSO), some sensitization campaigns are conducted within the community or professional and academic settings. These efforts do not cover the national territory and a large majority of Cameroonians are not yet informed and are continually exposed to risks factors of cancers (NSPCaPC, 2020;Roux et al 2021). This therefore makes it pertinent to determine the uptake of this preventive measures among women and determine the strategies that these women may prefer so as to increase uptake.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, under the private initiative of civil society organizations (CSO), some sensitization campaigns are conducted within the community or professional and academic settings. These efforts do not cover the national territory and a large majority of Cameroonians are not yet informed and are continually exposed to risks factors of cancers (NSPCaPC, 2020;Roux et al 2021). This therefore makes it pertinent to determine the uptake of this preventive measures among women and determine the strategies that these women may prefer so as to increase uptake.…”
Section: Introductionmentioning
confidence: 99%
“…Barriers were classified using the conceptual framework of Thaddeus' and Maine's three-delay model [15]. This framework was utilized in a previous study exploring the barriers to CC screening in Dschang district from the perspective of healthcare providers, enabling us to compare findings from both studies [16]. According to this model, the decision to seek healthcare can be classified into three delays.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, in a study conducted by Roux et al to examine the CC screening program in Dschang, HCPs reported that women's misconceptions about CC symptoms and prevention strategies explained why women did not access CC screening. According to Roux et al, improving health literacy also encompasses addressing fatalistic perceptions and stigma [16]. Because CC is perceived to be fatal, and sometimes viewed as a punishment, screening can stimulate emotions such as fear and shame.…”
Section: • Enhancing Health Literacymentioning
confidence: 99%
See 1 more Smart Citation
“…Technology and techniques for cervical cancer screening are improving. However, the uptake of programs is affected by factors including socio-economic issues, structural issues (such as distance to facilities and availability of transport) and sociocultural factors (such as psychological such as “fear of the results” or knowledge related barriers) [ 15 , 16 ]. Community healthcare workers (CHWs) can play an important role in overcoming these obstacles.…”
Section: Introductionmentioning
confidence: 99%